Methodical approaches for research of increase export competitiveness of Kazakhstan (International relations and international law Journal, 2016)
Development of measures to be hanged export competitiveness requires the processing of methodical approaches to explain why centain economic sectors are more successful in the export plan. Development of the economies of the member states of Eurasian union and Kazakhstan comes in a difficult situation in the global economy. Continuing high dependence of the economies of the Member States of the conjuncture of world market prices of energy making them stung by the global geopolitical context. Determines the direction of quantitative and qualitative growth of foreign trade, the scale and effectiveness of the participation of the Kazakhstan in the international division of labor in a globalizing world economy should be the diversification of expert potential. The article discusses the methodological approaches to the assessment of the export competitiveness of national economies and on this basis to make proposals on the enchance it to member countries of the Eurasian Economic Union.
Keywords: competitiveness; investment; environment; globalization; index; diversification; theory